Actitudes ambientales de la población en el Asentamiento Humano Aeropuerto. distrito de San Juan. Loreto. 2021 - Amacifuen Murayari, Alejandra Chabeli (2023)
The study on, environmental attitudes in the inhabitants of the human settlement Aeropuerto in the year 2021 had the objective of studying and evaluating the negative and positive attitudes of the population with respect to environmental conservation. This study used a non-experimental, prospective and simple descriptive research design. The target group for the survey was 1856 villagers who had at least 2 years of residence at the site. The sample included 128 inhabitants who were present during the use of the tool, inclusion and exclusion criteria were considered, the technique used was a survey, and the tool was a questionnaire of ten statements in positive and negative which passed through expert judgment for validity (Aiken validity index) and reliability tests (Crombach's alpha test). The data obtained, the analyses were carried out considering the objectives and hypotheses of the research, then represented in a Basic Data Matrix (BDM), analyzed, processed and tabulated using the SPSS version 25 statistical package. The main results show that differences were found in the general attitudes and their cognitive, affective and reactive components towards environmental conservation in the villagers. The general attitude and its cognitive, affective and reactive components towards environmental conservation was predominantly favorable. There is a high percentage of unfavorable and very unfavorable attitudes among the inhabitants according to sex and level of education. There is a lack of knowledge regarding conservation, classification of solid waste, active participation and affective and reactive actions in favor of environmental conservation, respectively.